Cavitation in shock wave lithotripsy: The critical role of bubble activity in stone breakage and kidney trauma - Bailey, MR; Cleveland, R; Colonius, T; Crum, L; Evan, A; Lingeman, J; McAteer, J; Sapozhnikov, O; Williams, J (2003)
A study of the physical mechanisms responsible for the stone comminution and tissue injury in the shock wave lithotripsy (SWL) was presented. The SWL is a common and effective clinical method to comminute the kidney stones. It was found that the treatment at slow SW (shock waves) rate increased the cavitation bubbble cluster time to dissolve between the pulses and increased the comminution. The results show that the role of cavitation in SWL was embraced by the lithotripter industry.